Synchronous gallbladder perforation and appendicitis in a pediatric patient - José Miguel Aceves-Ayala; Pablo Francisco Rojas-Solís; Ashley Yael Sotelo-Casas; Yazmín Areli Sánchez-Reynoso; Carlos Alfredo Bautista-López (Elsevier, 2022)
Background: Acute appendicitis and acute cholecystitis are among the most common diagnoses operated by general surgeons. However, synchronous appendicitis and cholecystitis have rarely been reported and most cases have been described as acalculous cholecystitis and appendicitis in early stages that are not absolutely synchronous. We report a case of a fourteen-year-old male patient who presented acute acalculous cholecystitis with gallbladder perforation at the time of a laparoscopic appendectomy for acute appendicitis. Discussion: Acute acalculous cholecystitis is an acute necroinflammation of the gallbladder in the absence of gallstones. In the pathophysiology the main factor is gallbladder wall ischemia with microcirculation failure and biliary stasis. There is discussion about the coexistence of acute appendicitis with acute cholecystitis with a presumed pathophysiological relationship; however, this is not well described. In this case it was found an acute acalculous cholecystitis in advanced stages with gallbladder perforation and a synchronous presentation of acute appendicitis. Conclusions: The synchronous presentation of acute appendicitis and cholecystitis with its complications, such as spontaneous perforation, is rare, but should be considered as a cause of acute abdomen with a pathophysiology still unknown.